Sleep disorders in patients with overweight and acute and exacerbated chronic heart failure. (3rd May 2023) - Kalaydzhiev, P; Kinova, E; Somleva, D; Borizanova, A; Poroyliev, N; Goudev, A
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Medical University - Sofia Background: Often accompanying comorbidity in patients with acute heart failure and overweight is sleep disorders. Searching and treatment of sleep apnea will be helpful in these patients. CPAP therapy may improve the prognosis. Purpose: To determine the frequency and the phenotypic characteristics and of sleep apnea in patients with overweight and exacerbated heart failure. To add continuous positive airway pressure (CPAP) therapy in patients with obstructive sleep apnea (OSA) and monitor changes in systolic and diastolic function. To assess the survival rate in CPAP therapy group and the control group. Methods: 100 consecutive patients hospitalized for exacerbation heart failure in the cardiology department. After the selection, 61 patients meet inclusion criteria – Apnea-Hypopnea index (AHI) > 5, Epworth Sleepiness Scale (ESS) > 6, NTproBNP>900 pg/ml, and Body mass index(BMI) >25. All patients receiving optimal medical treatment. The follow-up period was 2 years. The primary endpoint was death for any reason. Sleep apnea screening was performed with ApneaLinkTM. Echocardiographic assessment of left ventricular ejection fraction (LVEF) and the E/e'm ratio. Results: From 61 with sleep disorders 82% (n=50) has OSA and 18% (n=11) has central sleep apnea (CSA). Detected significant changes in LVEF between the OSA group and CSA group (EF% 49.6±8.5vs41.8±11.4;p=0.013). Also statistical significant changes there was about E/e'm ratio and BMI (BMI-38.5±7.1vs31.9±4.5;p=0.005 and E/e'm-17.1±3.7vs20.9±2.5;p=0.002)(Tab. 1). We found a strong reverse correlation between the LVEF and the number of central sleep apnea events (r=-0, 52;p<0, 001). There was a strong correlation between BMI and ESS (r=0, 649;p<0, 001). In the OSA group, CPAP therapy was started in 13 patients, the rest of the group (n=37) continue on optimal medication therapy. At the end of the follow-up period in statistical analysis were included 11 patients from the CPAP group and 20 patients from the control group. There was improvement about LVEF, ESS and BMI in CPAP group at end of follow-up (EF%-start: 46, 82±9, 61vs end of study:49, 45±8, 23;p=0, 019, ESS–start 13±2, 6vs end of study 5, 9 ±1, 5;p<0, 001, BMI–start: 39, 9±5, 6vs end of study: 35, 9±4, 4;p=0, 001). There were no significant changes in E/e'm ratio (E/e'm:start 16, 3±3, 2vs end of study:15±5, 1;p=0, 327). In the control group, there were no significant changes. Kaplan-Meier analysis confirmed that the CPAP group has a better survival rate than the control group in the follow-up period (Log-Rank p=0.049). Conclusions: Obstructive sleep apnea was more common in obese heart failure patients. The left ventricular systolic function is lower in patients with central sleep apnea. Additional CPAP treatment can improved ejection fraction in patients with heart failure and obstructive sleep apnea. There is a positive effect on BMI. Base on ESS, subjective daytime sleepiness was improved. CPAP therapy can improve the survival rate.